Cardiac tamponade caused by an ingested sewing needle. A case report - Cekirdekci, Ahmet; Ayan, E.; Ilkay, E.; Yildirim, H. (My University, 2003)
Ingested sharp-pointed foreign bodies can cause serious complications. A case of a 16-year-old girl with cardiac tamponade due to ingestion of a sewing needle is presented. Ingested needles have often been reported as a cause of gastrointestinal injuries but in this rare case the sewing needle actually migrated into the myocardium.
Keywords: Cardiac tamponade, etiology; Cardiac tamponade, surgery; Foreign bodies